An improved look-up table-based direct torque control for permanent magnet synchronous generator using Vienna rectifier. (June 2022) - Yip, Sook Yee; Che, Hang Seng; Tan, Chee Pin; Chong, Wen Tong
Highlights: Development of the PMSG model related to the Vienna rectifier for analytical investigation of the effect of switching vectors. Improved look-up table-based direct torque control was developed to control a permanent magnet synchronous generator using Vienna rectifier. Model-based computational delay compensation approach for the digital implementation of direct torque control. Irregular torque and stator flux ripples especially during unbalance DC load connection was addressed. Laboratory scale model developed using Texas Instrument TMS320F28335 and tested with wind turbine emulator as a wind energy conversion system. Abstract: This paper presents an improved look-up table-based direct torque control of the permanent magnet synchronous generator using Vienna rectifier for a wind energy conversion system. A stator voltage model for the system was developed to allow an in-depth analysis of the effect of the switching vectors for the Vienna rectifier on the performance of direct torque control. The developed generator model is dedicated to reducing the complexity of look-up table development. Subsequently, an improved look-up table was designed to enhance the overall performance of the permanent magnet synchronous generator in both torque and stator flux ripples, along with the investigation of the computation delay compensation for the digital implementation. The performance was first investigated through Matlab / Simulink before being further validated using a small-scale prototype and a wind turbine emulator. Both simulation and experimental results obtained were compared with the existing direct torque control approach to verify the effectiveness of the proposed system for wind energy extraction. The results show that the enhanced look-up table generates lower ripples in torque and stator flux while improving their reference tracking, especially during unbalanced DC load scenarios. This achievement can be clearly seen by the lower discrepancy percentage between the reference and actual value in the generated torque and stator flux by 6.35% and 0.47%, respectively.